Water-based negative electrode binder for lithium ion battery, preparation method and application of water-based negative electrode binder

Through a new preparation method of aqueous negative electrode binder, pre-emulsification and solubilization emulsion technology is used to form emulsion polymers and water-soluble polymer composite ligands with stronger binding force, solving the brittleness and demulsification risks of lithium-ion battery negative electrode binder during processing, and achieving higher processing flexibility and stability.

CN119823681APending Publication Date: 2025-04-15WANHUA CHEM GRP BATTERY TECH CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411929847.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-26
Publication Date
2025-04-15

AI Technical Summary

Technical Problem

The existing lithium-ion battery negative electrode binders have problems such as high brittleness during processing and easy cracking and powder loss during processing. There is a risk of demulsification during emulsion dispersion, which affects the uniformity and stability of the slurry.

Method used

A new method of preparing aqueous negative electrode binder is adopted, through pre-emulsification and solubilization emulsion technology, combined with monomer solution polymerization and the use of initiators, an emulsion polymer and water-soluble polymer composite ligand with stronger binding force is formed, avoiding the risk of emulsification and improving the shear resistance and flexibility of processing.

Benefits of technology

This method significantly improves the processing flexibility of the negative electrode sheet of lithium-ion battery, reduces energy utilization, avoids the risk of demulsification, ensures the stability and performance of the negative electrode sheet, and solves the brittleness and cracking problems of traditional binders during processing.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005210010870000041
    Figure BDA0005210010870000041
  • Figure BDA0005210010870000061
    Figure BDA0005210010870000061
Patent Text Reader

Abstract

The invention discloses a preparation method and application of a water-based negative electrode binder for a lithium ion battery. The method comprises the following steps: (1) pre-emulsifying an emulsifier, water, an aromatic vinyl monomer, an acrylate monomer and a functional monomer to obtain a pre-emulsion, and preparing an initiator aqueous solution; (2) adding water and an emulsifier into the bottom of the reaction kettle and stirring; then, dropwise adding the pre-emulsion and an initiator aqueous solution for reaction, and obtaining a solubilizing emulsion after the reaction is finished; (3) adding water into the solubilizing emulsion for diluting and uniformly mixing; (4) adding an acrylic monomer, an acrylonitrile monomer and an acrylamide monomer into a monomer tank to prepare a monomer aqueous solution, and adding an initiator into an initiator tank to prepare an initiator aqueous solution; (5) synchronously dropwise adding a monomer aqueous solution and an initiator aqueous solution into the kettle containing the solubilizing emulsion in the step (3), and keeping the temperature after dropwise adding is finished; and (6) finishing heat preservation, adding a proper amount of alkali liquor into the reaction kettle, and adjusting the pH value to 6-9 to obtain the target water-based binder. The two components of the prepared adhesive have good compatibility and good mechanical stability, and the prepared negative pole piece has relatively high cohesive strength, high adhesive strength and good processing flexibility.
Need to check novelty before this filing date? Find Prior Art

Description

Technical field:

[0001] The invention belongs to the technical field of polymer materials, and specifically relates to an aqueous binder, and in particular to an aqueous negative electrode binder for a negative electrode of a lithium ion battery. Background technology:

[0002] Lithium-ion batteries have the advantages of high energy density and long cycle life, and are widely used in portable electronic devices, electric vehicles, energy storage and other fields. At present, lithium-ion batteries are mainly composed of positive electrode sheets, negative electrode sheets, electrolytes, diaphragms, shells, etc. Their working principle is to store and release electrical energy through the redox reaction of reversible embedding / de-embedding of lithium ions in electrode active materials.

[0003] The negative electrode of lithium-ion batteries is made of graphite and conductive agent as the main active materials, and water-dispersible polymers such as sodium carboxymethyl cellulose (CMC), polyacrylic acid (PAA), styrene-butadiene latex (SBR) or styrene-acrylic emulsion (PA) or polyvinylidene fluoride (PVDF) as binders. The slurry is prepared by mixing and coating on the current collector copper foil and drying. Compared with oily binders, water-based binders have the advantages of safety, no pollution, low production energy consumption, and easy operation.

[0004] In the process of using pure SBR or PA emulsion in the prior art, a large amount of CMC needs to be added as a thickener and dispersant, but CMC has low bonding performance, high brittleness, and high internal resistance; at the same time, the pure emulsion system has low bonding force and large swelling, which can easily destroy the negative electrode graphite structure during the lithium battery cycle, leading to deterioration of battery performance or causing other safety risks. During the use of the pure PAA system, the bonding strength is high and the swelling when immersed in the electrolyte is low, but the PAA binder has a high glass transition temperature, and the electrode is prone to cracking and powder loss during cutting during the processing process, which restricts the use of pure PAA. When using PAA, the industry generally compound SBR or PA emulsions, which has a cumbersome processing process and there is a risk of demulsification during the emulsion dispersion process.

[0005] CN 118325523 A discloses a high molecular weight aqueous acrylic copolymer adhesive, which is prepared by first mixing water and acrylic monomers, adjusting the neutralization degree of the acid monomer aqueous solution to be greater than or equal to 50% and less than 100%, and then polymerizing with acrylonitrile monomers, acrylamide monomers and selective acrylate monomers to obtain an acrylic copolymer aqueous solution. Although the acrylic copolymer prepared in this patent has a higher molecular weight and does not require precipitation polymerization, the product still has problems such as high brittleness and easy cracking and powdering during processing when used in negative electrode plates.

[0006] CN 118344826 A discloses a lithium ion battery negative electrode aqueous binder with excellent low temperature performance, which is composed of polymer microparticle emulsion A and water-soluble polymer B in a certain proportion. The polymer microparticle emulsion A is a polymer microparticle dispersion prepared by emulsion copolymerization of conjugated diene monomers, aromatic vinyl monomers, other monomers that can be free radical copolymerized, and functional monomers; the water-soluble polymer B is a multi-component copolymer prepared by dispersion polymerization or precipitation polymerization with acid and / or acid salt functional monomers, nitrile functional monomers, and a third functional group as main monomers, and is neutralized with an alkali to form a polymer aqueous solution. The polymer microparticle emulsion A and the water-soluble polymer B are mixed according to the solid content contained in the ratio of 95:5 to 30:70 to form an aqueous binder. In this patent, the binder is compounded by emulsion A and water-soluble polymer B. Emulsion A is prone to demulsification during the dispersion process of lithium-ion battery negative electrode slurry, affecting the uniformity and stability of the slurry. Water-soluble polymer B is prepared by precipitation polymerization, has a low molecular weight, and produces a large amount of wastewater during the washing process. Summary of the invention:

[0007] In order to solve the above technical problems, the purpose of the present invention is to provide a lithium ion battery aqueous negative electrode binder, a preparation method and its application. Compared with traditional PAA products, the binder has better processing flexibility and higher energy utilization compared with precipitation polymerization process. At the same time, compared with the simple physical blending of emulsion polymer and water-soluble polymer, the binder emulsion polymer and water-soluble polymer have a stronger combination, no risk of demulsification during use, and both shear resistance and flexibility in processing.

[0008] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:

[0009] In one aspect, the present invention provides a method for preparing an aqueous negative electrode binder for a lithium ion battery, the method comprising the following steps:

[0010] (1) pre-emulsifying an emulsifier, water, an aromatic vinyl monomer, an acrylate monomer, and a functional monomer to obtain a pre-emulsion, and simultaneously preparing an initiator aqueous solution;

[0011] (2) adding water and an emulsifier to the bottom of the reaction kettle and stirring; then, adding the pre-emulsion and the initiator aqueous solution dropwise to react, and obtaining a solubilized emulsion after the reaction is completed;

[0012] (3) adding water to the solubilized emulsion to dilute and mix well;

[0013] (4) adding acrylic acid monomer, acrylonitrile monomer and acrylamide monomer into a monomer tank to prepare a monomer aqueous solution, and adding an initiator into an initiator tank to prepare an initiator aqueous solution;

[0014] (5) dropping the monomer aqueous solution and the initiator aqueous solution simultaneously into the kettle containing the solubilized emulsion in step (3), and keeping the temperature after the dropping is completed;

[0015] (6) After the heat preservation is completed, add an appropriate amount of alkali solution into the reactor to adjust the pH value to 6-9 to obtain the target water-based adhesive.

[0016] In a preferred experimental scheme, the pre-emulsion in step (1) comprises the following raw materials (by mass ratio): 0.1-0.5% emulsifier, 20-40% water, 20-40% aromatic vinyl monomer, 20-40% acrylate monomer and 5-10% functional monomer.

[0017] In a preferred experimental scheme, the emulsifier in step (1) is selected from a surfactant containing at least one ethylenically unsaturated functional group, preferably at least one of allyloxy isoalcohol ether sulfate ammonium salt, allyl polyether phosphate, allyl special thiol sulfate, allyl polyoxyalkylene ether sulfate, allyl alkyl succinate sulfonate, allyl ether hydroxypropane sulfonate, and polyoxyethylene styrenated phenyl ether sulfate.

[0018] In a preferred experimental scheme, the aromatic vinyl monomer in step (1) is selected from styrene, α-methylstyrene, 4-tert-butylstyrene, vinyl chloride benzene, vinyl toluene, or a mixture of two or more thereof in any proportion.

[0019] In a preferred experimental scheme, the acrylic ester monomer in step (1) is selected from one or a mixture of any proportion of methyl acrylate, ethyl acrylate, butyl acrylate, butyl methacrylate, isooctyl acrylate, and methyl methacrylate.

[0020] In a preferred experimental scheme, the functional monomer in step (1) comprises one or more of acrylic acid, methacrylic acid, itaconic acid, acrylamide and acrylonitrile, preferably acrylic acid.

[0021] In a preferred experimental scheme, the raw materials used in the preparation of the solubilized emulsion in step (2) are as follows: 30-50% water, 0.1-0.5% emulsifier, 50-70% pre-emulsion, and 0.01-1% initiator in terms of mass ratio.

[0022] In a preferred experimental scheme, the emulsifier in step (2) is selected from a surfactant containing at least one ethylenically unsaturated functional group, preferably selected from at least one of allyloxy isomeric alcohol ether sulfate ammonium salt, allyl polyether phosphate, allyl-containing special thiol sulfate, allyl polyoxyalkylene ether sulfate, allyl alkyl succinate sulfonate, allyl ether hydroxypropane sulfonate, and polyoxyethylene styrenated phenyl ether sulfate.

[0023] In a preferred experimental scheme, the initiator in step (2) is selected from at least one of ammonium persulfate, sodium persulfate, potassium persulfate, ammonium persulfate and isoascorbic acid, hydrogen peroxide and sodium bisulfite.

[0024] In a preferred experimental scheme, the reaction temperature in step (2) is 70-90° C., and the dropwise addition time is 1-2 hours.

[0025] In a preferred experimental scheme, the mass ratio of the solubilized emulsion to the added water in step (3) is 30:70 to 70:30, and the stirring time is 10-30 minutes.

[0026] In a preferred experimental scheme, in the step (4), the acrylic monomer is at least one of acrylic acid and methacrylic acid; the acrylonitrile monomer is at least one of acrylonitrile and methacrylonitrile; and the acrylamide monomer is at least one of acrylamide, N-methylacrylamide, N-ethylacrylamide, and N-butylacrylamide.

[0027] In a preferred experimental scheme, the mass ratio of acrylic acid monomer: acrylonitrile monomer: acrylamide monomer in the monomer aqueous solution in step (5) is 20-40: 20-40: 5-20%; in a preferred experimental scheme, the amount of initiator used in step (5) accounts for 0.01-1% of the total mass of the monomers.

[0028] In a preferred experimental scheme, the mass ratio of the total monomers in the monomer aqueous solution in step (5) to the total monomers in the solubilized emulsion in step (2) is 80:20 to 20:80, for example 70:30, 60:40, 50:50, 40:60, 30:70.

[0029] In a preferred experimental scheme, the dripping time of the monomer aqueous solution and the initiator aqueous solution in step (5) is 120-240 min; the insulation time is 60-120 min, and the insulation temperature is 70-90°C.

[0030] In a preferred experimental scheme, the alkali solution in step (6) is selected from inorganic alkali metal compounds, preferably one or more of sodium hydroxide, potassium hydroxide, lithium hydroxide, lithium carbonate, sodium carbonate, and potassium carbonate, and the concentration is 5-15wt%.

[0031] Another aspect of the present invention provides a negative electrode binder prepared by the above method, wherein the solid content of the negative electrode binder is 1-25%, preferably 5-15%.

[0032] Finally, the present invention provides the application of the negative electrode binder in the negative electrode plate of a lithium ion battery. Specific implementation method:

[0033] The present invention will be further described below through specific embodiments. The specific embodiments are only detailed descriptions of the contents of the present invention, but not limiting the scope of the present invention.

[0034] Table 1: Main raw materials and sources

[0035]

[0036] Unless otherwise specified, other chemical reagents used in the examples were purchased from the market and were of analytical grade.

[0037] Example 1

[0038] (1) pre-emulsifying 0.2 g of allyloxy isomeric alcohol ether sulfate ammonium salt, 40 g of deionized water, 30 g of styrene, 25 g of butyl acrylate and 5 g of acrylic acid to obtain a pre-emulsion, and dissolving 0.1 g of sodium persulfate in 10 g of deionized water to obtain an initiator aqueous solution;

[0039] (2) adding 90 g of water and 0.2 g of ammonium salt of allyloxy isomeric alcohol ether sulfate to the bottom of the reaction kettle, starting stirring, setting the speed to 200 r / min, and raising the temperature to 80° C.; then, dropping 100 g of the pre-emulsion and 10 g of the initiator aqueous solution to react for 100 minutes, and the reaction is completed to obtain a solubilized emulsion;

[0040] (3) Add 200 g of water to the solubilized emulsion for dilution and stir for 20 min;

[0041] (4) adding 6 g of acrylic acid, 6 g of acrylonitrile, 3 g of acrylamide and 5 g of deionized water into a monomer tank to prepare a monomer aqueous solution, and adding 0.02 g of sodium persulfate and 10 g of deionized water into an initiator tank to prepare an aqueous solution;

[0042] (5) 20 g of monomer aqueous solution and 10 g of initiator aqueous solution were simultaneously added dropwise into the kettle at a reaction temperature of 80° C. for 120 min. After the addition was completed, the temperature was kept at 80° C. for 60 min.

[0043] (6) After the heat preservation is completed, lithium hydroxide aqueous solution (15% by mass) is added to the reactor to adjust the pH value to 7.5, and water is added to adjust the solid content to 6% to obtain the target aqueous negative electrode binder.

[0044] Example 2

[0045] Similar to Example 1, except that the addition amounts of acrylic acid, acrylonitrile, acrylamide and deionized water in step (4) are increased, and the specific raw material ratios are shown in Table 2, and the dropping time in step (5) is extended to 180 min, and the insulation time is extended to 90 min.

[0046] Example 3

[0047] Similar to Example 1, except that the addition amounts of acrylic acid, acrylonitrile, acrylamide and deionized water in step (4) are increased, and the specific raw material ratios are shown in Table 2, and the dropping time in step (5) is extended to 240 min, and the insulation time is extended to 120 min.

[0048] Example 4

[0049] Similar to Example 2, except that the amounts of styrene, butyl acrylate, acrylic acid and sodium persulfate added in step (1) are adjusted. The specific raw material ratios are shown in Table 2; the reaction temperature in step (2) is adjusted to 70° C., and the reaction time is adjusted to 240 min.

[0050] Example 5

[0051] Similar to Example 2, except that the addition amount of styrene and acrylic acid in step (1) is adjusted, butyl acrylate is replaced with isooctyl acrylate and the addition amount is adjusted, and the specific raw material ratio is shown in Table 2; the reaction temperature in step (2) is adjusted to 90°C, and the reaction time is adjusted to 120 min. The addition amount of deionized water in step (3) is adjusted to 90 g.

[0052] Example 6

[0053] Similar to Example 2, except that butyl acrylate in step (1) is replaced with isooctyl acrylate, and the specific raw material ratio is shown in Table 2; the added amounts of acrylic acid, acrylonitrile and acrylamide in step (4) are adjusted, and the specific raw material ratio is shown in Table 2.

[0054] Example 7

[0055] Similar to Example 2, except that the amounts of acrylic acid, acrylonitrile and acrylamide added in step (4) are adjusted. The specific raw material ratios are shown in Table 2.

[0056] Comparative Example 1

[0057] The method is similar to Example 1, except that after the reaction of step (2) is completed, a lithium hydroxide aqueous solution (15% by mass) is used to adjust the pH value to 7.5, and step (3) is omitted; step (5) is changed to dropwise adding a monomer aqueous solution and an initiator aqueous solution into another reactor, and after the reaction is completed, the precipitate is filtered out, washed twice with deionized water, and the pH value is adjusted to 7.5 with a lithium hydroxide aqueous solution (15% by mass); the products obtained in step (2) and step (5) are transferred to the same reactor, stirred at 500 r / min, and blended for 30 min.

[0058] Comparative Example 2

[0059] Similar to Example 1, the difference is that the amount of acrylic acid, acrylonitrile, acrylamide and deionized water added in step (4) is increased, the specific raw material ratio is shown in Table 2, and the dropwise addition time in step (5) is extended to 240 minutes, and the insulation time is 120 minutes. Due to the limited solubilization effect of the solubilizing emulsion, a precipitate is precipitated by the reaction. After the reaction is completed, it is washed twice with deionized water, and the pH value is adjusted to 7.5 with a lithium hydroxide aqueous solution (15% mass fraction), and water is added to adjust the solid content to 6%.

[0060] Comparative Example 3

[0061] A commercially available acrylic acid multi-polymer aqueous solution, Indile LA136DL water-based adhesive, was used.

[0062] Comparative Example 4

[0063] A commercially available styrene acrylic emulsion, Showa LB300J, was used.

[0064] Table 2: Ratio of raw materials in the reaction of the implementation case

[0065]

[0066] The emulsion binder prepared in the embodiment and the comparative example is applied to the preparation of the negative electrode plate of a lithium ion battery, and the specific steps are as follows:

[0067] (1) Slurry preparation: 0.5 g of sodium carboxymethyl cellulose was added to 100 g of deionized water at room temperature and stirred at high speed for about 20 minutes. Then, 1 part of carbon black conductive agent, 96.5 g of negative electrode active material graphite and 2 g of negative electrode binder were added respectively. After adding each material, it was stirred at high speed for more than 10 minutes to mix evenly. After filtering through a 100-mesh filter, the negative electrode slurry was obtained.

[0068] (2) Pole sheet coating: The prepared negative electrode slurry was evenly coated on the copper foil with a coating thickness of 100 μm, placed in a 90°C oven for drying for 5 minutes, and rolled on a roller press at room temperature to obtain a negative electrode sheet with a thickness of 65 μm.

[0069] Experimental data:

[0070] (1) Mechanical stability test: Pour 1000 g of the negative electrode binder sample into a suitable container (about 50% by volume), stir using a high-speed disperser (the stirring head is disc-shaped with a diameter of about 100 mm), adjust the speed to 3000 r / min, disperse for 0.5 h, filter using a 325-mesh filter, and use tap water to flush the residue on the inner wall of the container into the filter to observe whether the emulsion is broken and whether there are obvious flocculants.

[0071] (2) Peel strength evaluation: The test is performed by a special adhesion tester. The test method of peel strength refers to the American Society for Testing and Materials standard ASTM D3330. The instrument is a Kejian tensile testing machine. The details are as follows: Cut the negative electrode into a 150mm long and 15mm wide electrode along the rolling direction. Stick a 3M double-sided tape with a length of 100mm and a width of 15mm on a smooth stainless steel plate, stick the electrode flat on the double-sided tape, and roll it back and forth 10 times with a 2 kg rubber roller. Then fix the stainless steel plate on the tensile machine, and clamp the electrode not attached to the tape in the opposite direction on the tensile machine probe. The tensile machine base pulls the electrode at a speed of 5cm / min, and the sensor measures the peel force during this process. The average value of each group of 5 parallel samples is the final peel strength. Peel force = computer reading / 0.015, unit is N / m.

[0072] (3) The flexibility of the negative electrode plate is evaluated by the following method: a core rod with a diameter of Φ = 1.0 mm is placed on the current collector side of the rolled electrode plate of the embodiment and the comparative example, and a bending test is performed. The state of the electrode plate at this time is observed under an optical microscope. A good electrode plate is marked as √, and a electrode plate that has fallen off or cracked is marked as ×.

[0073] Table 4: Adhesive performance test data

[0074] Polymerization stability Mechanical stability Peel strength N / m Pole flexibility Embodiment 1 normal normal 5.5 √ Embodiment 2 normal normal 8.8 √ Embodiment 3 normal normal 13.3 √ Embodiment 4 normal normal 9.1 √ Embodiment 5 normal normal 8.9 √ Embodiment 6 normal normal 9.4 √ Embodiment 7 normal normal 8.5 √ Comparative Example 1 precipitation Demulsification 7.9 √ Comparative Example 2 Slag discharge normal 5.5 × Comparative Example 3 / normal 12.1 × Comparative Example 4 / Demulsification 5.2 √

[0075] It can be seen from the mechanical stability test results of comparative examples 1 and 4 that after simply physically blending the styrene-acrylic emulsion and the polyacrylic copolymer, the bonding effect between the emulsion and the solution is poor, and the latex particles are still exposed in the phase, which has the risk of demulsification, which is not conducive to the processing of lithium battery slurry; it can be seen from the polymerization stability of comparative example 2 that within a certain proportion, the latex particles of the solubilized emulsion can provide solubilization and dispersion for the polyacrylic copolymer, no precipitation will be produced during the reaction, no washing is required, and there is a certain coating and bonding between the latex particles and the polyacrylic copolymer molecular chains, and there is no risk of demulsification during the mechanical stirring process. It can be seen from the flexibility of comparative example 3 that the pole piece flexibility of the polyacrylic copolymer is still poor, which greatly limits its application in lithium-ion batteries. It can be seen that the negative electrode adhesive prepared by the step-by-step polymerization process has a stronger bond between the emulsion polymer and the water-soluble polymer, no risk of demulsification during use, and has both the shear resistance of processing and the flexibility of the pole piece.

Claims

1. A method for preparing an aqueous negative electrode binder for a lithium ion battery, the method comprising the following steps: (1) pre-emulsifying an emulsifier, water, an aromatic vinyl monomer, an acrylate monomer, and a functional monomer to obtain a pre-emulsion, and simultaneously preparing an initiator aqueous solution; (2) adding water and an emulsifier to the bottom of the reaction kettle and stirring; then, adding the pre-emulsion and the initiator aqueous solution dropwise to react, and obtaining a solubilized emulsion after the reaction is completed; (3) adding water to the solubilized emulsion to dilute and mix well; (4) adding acrylic acid monomer, acrylonitrile monomer and acrylamide monomer into a monomer tank to prepare a monomer aqueous solution, and adding an initiator into an initiator tank to prepare an initiator aqueous solution; (5) dropping the monomer aqueous solution and the initiator aqueous solution simultaneously into the kettle containing the solubilized emulsion in step (3), and keeping the temperature after the dropping is completed; (6) After the heat preservation is completed, add an appropriate amount of alkali solution into the reactor to adjust the pH value to 6-9 to obtain the target water-based adhesive.

2. The preparation method according to claim 1, characterized in that In terms of mass content, the pre-emulsion in step (1) comprises the following raw materials: 0.1-0.5% emulsifier, 20-40% water, 20-40% aromatic vinyl monomer, 20-40% acrylate monomer and 5-10% functional monomer.

3. The preparation method according to claim 1 or 2, characterized in that: In the step (1), the emulsifier is selected from a surfactant containing at least one ethylenically unsaturated functional group, preferably at least one of allyloxy isomeric alcohol ether sulfate ammonium salt, allyl polyether phosphate, allyl special mercaptan sulfate, allyl polyoxyalkylene ether sulfate, allyl alkyl succinate sulfonate, allyl ether hydroxypropane sulfonate, and polyoxyethylene styrenated phenyl ether sulfate; and / or, in the step (1), the aromatic vinyl monomer is selected from styrene, α-methylstyrene, 4-tert-butylstyrene, vinyl chloride benzene, vinyl toluene, and a mixture of two or more thereof in any proportion.

4. The preparation method according to any one of claims 1 to 3, characterized in that: In the step (1), the acrylate monomer is selected from one or a mixture of any proportion of methyl acrylate, ethyl acrylate, butyl acrylate, butyl methacrylate, isooctyl acrylate, and methyl methacrylate; and / or, the functional monomer in the step (1) comprises one or more of acrylic acid, methacrylic acid, itaconic acid, acrylamide, and acrylonitrile, preferably acrylic acid.

5. The preparation method according to any one of claims 1 to 4, characterized in that: In the preparation of the solubilized emulsion in step (2), the raw materials used in the mass ratio are: 30-50% water, 0.1-0.5% emulsifier, 50-70% pre-emulsion, and 0.01-1% initiator; and / or, the reaction temperature in step (2) is 70-90° C. and the dropwise addition time is 1-2 hours.

6. The preparation method according to any one of claims 1 to 5, characterized in that: In the step (2), the emulsifier is selected from a surfactant containing at least one ethylenically unsaturated functional group, preferably selected from at least one of allyloxy isoalcohol ether sulfate ammonium salt, allyl polyether phosphate, allyl special mercaptan sulfate, allyl polyoxyalkylene ether sulfate, allyl alkyl succinate sulfonate, allyl ether hydroxypropane sulfonate, and polyoxyethylene styrenated phenyl ether sulfate; and / or, the initiator in the step (2) is selected from at least one of ammonium persulfate, sodium persulfate, potassium persulfate, ammonium persulfate and isoascorbic acid, hydrogen peroxide and sodium bisulfite.

7. The preparation method according to any one of claims 1 to 6, characterized in that: In the step (3), the mass ratio of the solubilized emulsion to the added water is 30:70 to 70:30; and / or the stirring time is 10-30 min; and / or, in the step (4), the acrylic acid monomer is at least one of acrylic acid and methacrylic acid; the acrylonitrile monomer is at least one of acrylonitrile and methacrylonitrile; and the acrylamide monomer is at least one of acrylamide, N-methylacrylamide, N-ethylacrylamide, and N-butylacrylamide.

8. The preparation method according to any one of claims 1 to 7, characterized in that: In the step (5), the weight ratio of acrylic acid monomer: acrylonitrile monomer: acrylamide monomer is 20-40:20-40:5-20%; and / or, the amount of initiator used in the step (5) accounts for 0.01-1% of the total weight of the monomers; and / or, the weight ratio of the total monomers in the monomer aqueous solution in the step (5) to the total monomers in the solubilized emulsion in the step (2) is 80:20 to 20:80; and / or, the dropwise addition time of the monomer aqueous solution and the initiator aqueous solution in the step (5) is 120-240 minutes; the heat preservation time is 60-120 minutes, and the heat preservation temperature is 70-90°C.

9. The negative electrode binder prepared by the preparation method according to any one of claims 1 to 8, wherein the solid content of the negative electrode binder is 1-25%, preferably 5-15%.

10. Use of the negative electrode binder prepared by the preparation method according to any one of claims 1 to 8 or the negative electrode binder according to claim 9 in a negative electrode sheet of a lithium ion battery.

Citation Information

Cited By

  • Aqueous binder for negative electrode of lithium ion battery as well as preparation method and application of aqueous binder

    CN122255909A